Pengembangan Ekotourism untuk Pemanduwisata Kabupaten Klungkung, Bali - KOESWIRYONO, DIKA PRANADWIPA; SULASMINI, NI MADE AYU; ANTARA, IDA BAGUS KETUT SOMA (LOSARI DIGITAL, 2025)
Tourist guides need to improve their competence in interpreting a tourism site. The ecotourism tour guide training program initiated by the Tourism Office of Klungkung Regency aims to enhance the quality of tour guides in the region. With the goal of providing unique and memorable tourism experiences for tourists, this program contributes to the development of tourism potential and local economic growth. The training is attended by forty prospective tour guides from diverse backgrounds and interests. Collaborating with lecturers from the Institute of Tourism and International Business in Denpasar as speakers, the program prioritizes the quality and professionalism of content delivery. Discussions encompass critical aspects of tour guiding, including designing effective tours and building positive relationships within the context of tourism. Participants are provided training in formulating engaging and relevant tour materials, along with opportunities to practice presenting their own content. The implementation stages of the Community Engagement (PkM) program include pre-implementation, execution, and evaluation. The Focus Group Discussion (FGD) involves various stakeholders in discussing issues faced by tourism villages in Klungkung Regency regarding tourism development, aiming to identify problems and solutive steps. The education method is employed during the execution phase to enhance participants' ability to access relevant information, supplemented with pre- and post-tests to measure comprehension. The evaluation stage encourages participants to apply learned guiding techniques and receive feedback from the speakers. The execution of this program is intended to create a positive impact in the tourism sector of Klungkung Regency, employing a systematic approach that identifies issues and applies practical solutions. The engagement activities showcase active participant interaction in gaining knowledge about effective tour design and practical guiding skills. Therefore, this program is anticipated to elevate the quality of local tourism with skilled and knowledgeable tour guides, providing meaningful experiences for tourists visiting Klungkung Regency.